Diseño del trabajo de aula: un proceso fundamental hacia la profesionalización de la acción docente - García-Martínez, Álvaro; Hernandez Barbosa, Rubinsten; Abella-Peña, Leonardo (Revista Científica, 2018)
In this paper, some ideas are presented on the aspects that need to be considered in the planning, design, implementation and evaluation of a didactic unit. The importance of understanding the elements that constitute it and its articulation with the objectives, resources, and activities proposed in its development are emphasized. In addition, it is intended to highlight how relevant is the exercise of planning, design and evaluation done by teachers, as a space for reflection, reconstruction, and qualification of their teaching practice. An important contribution is the one related to the curriculum design map, which, since our point of view, is fundamental when it comes to guiding the teaching and learning processes. Some reflections on the importance of the development of cognitive-linguistic skills and the use of new technologies in the design, development, and evaluation of didactic units are also presented.